2013
DOI: 10.5694/mja12.11854
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome care across Australia and New Zealand: the SNAPSHOT ACS study

Abstract: This first comprehensive combined Australia and New Zealand audit of ACS care identified variations in the application of the ACS evidence base and varying rates of inhospital clinical events. A focus on integrated clinical service delivery may provide greater translation of evidence to practice and improve ACS outcomes in Australia and New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
142
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(163 citation statements)
references
References 25 publications
13
142
5
2
Order By: Relevance
“…in-hospital CABG, discharge with warfarin, in hospital major bleeding, diagnosis of unstable angina New Zealand, reported discharge prescription of a second antiplatelet drug in 63% of ACS patients [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in-hospital CABG, discharge with warfarin, in hospital major bleeding, diagnosis of unstable angina New Zealand, reported discharge prescription of a second antiplatelet drug in 63% of ACS patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…Yet as recently as 2012, a comprehensive Australian and New Zealand audit encompassing over 90% of hospitals across both countries showed that only 63% of ACS patients received a second antiplatelet agent at hospital discharge [8]. In all reported studies, one consistent observation was the difference between prescription of a second antiplatelet for patients following PCI (percutaneous coronary intervention), where rates were higher than for those undergoing CABG or medical management, despite a consistent accumulation of evidence supporting the use of these second agents in each of these contexts [9][10][11] There remains a significant risk of events following an ACS, with mortality in the [12][13][14][15][16][17][18] months following an ACS reported to be 12.6%, and the composite rate of myocardial infarction, stroke or cardiovascular death to be 18.3% [12,13]. Therefore, there is a…”
Section: Introductionmentioning
confidence: 99%
“…2 Two important studies investigating ACS in Australia and New Zealand over the last decade were the ACACIA Registry 14,15 and SNAPSHOT ACS Study. 16 Through a number of reports arising from these studies, an issue identified as of critical significance for the future reduction of morbidity and mortality from ACS was access to treatment. 13,16 Other studies have reported 30-40% of patients did not receive reperfusion therapy to which they were eligible, 17,18 which was similar to under-treated proportions of STEMI populations reported in North America 19 and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…16 Through a number of reports arising from these studies, an issue identified as of critical significance for the future reduction of morbidity and mortality from ACS was access to treatment. 13,16 Other studies have reported 30-40% of patients did not receive reperfusion therapy to which they were eligible, 17,18 which was similar to under-treated proportions of STEMI populations reported in North America 19 and Europe. 20 Despite the consistency in ACS guidelines across the United States, 21 Europe, 22 and Australia and New Zealand, 23,24 knowledge translation into clinical practice is often suboptimal.…”
Section: Introductionmentioning
confidence: 99%
“…28 Previous studies have lent weight to this assertion and have highlighted differences both in the medication and procedural domains. Using data collected from 1,400 patients aged 25-69 admitted to hospital in the lower Hunter region in NSW, Lim, O'Connell, and Heller found that patients admitted to metropolitan hospitals with AMI had shorter lengths of admission and greater use of beneficial medications (e.g., aspirin, ACE-inhibitors) compared with patients admitted to regional hospitals.…”
Section: Treatment Modalities and Clinical Outcomes Of Metropolitan Amentioning
confidence: 99%